Hysteria crime, media, and politics - Schuilenburg, Marc, 1971- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
According to the medical world, hysteria is a thing of the past, an outdated diagnosis that has disappeared for good. This book argues that hysteria is in fact alive and well. Hyperventilating, we rush from one incident into the next - there is hardly time for a breather. From the worldwide run on toilet paper to cope with coronavirus fears to the overheated discussions about immigration and overwrought reactions to the levels of crime and disorder around us, we live in a culture of hysteria. While hysteria is typically discussed in emotional terms - as an obstacle to be overcome - it nevertheless has very real consequences in everyday life. Irritating though this may be, hysteria needs to be taken seriously, for what it tells us about our society and way of life. That is why Marc Schuilenburg examines what hysteria is and why it is fuelled by a culture that not only abuses, but also encourages and rewards it. Written in a clear and direct style, this book will appeal to students and scholars of sociology, criminology, philosophy and all those interested in hysteria and how it permeates late modern society.
OCLC-licensed vendor bibliographic record.
Keywords: Hysteria -- History; PSYCHOLOGY / Social Psychology; SOCIAL SCIENCE / Criminology